Online media development of natural family planning - Asmawati Azis, Andi; Faridah Arsal, Andi; Bida Purnamasari, Andi (Journal of physics. Conference series, 2019)
This research aimed to develop natural family extension media online which can be used as alternative method of family planning, to know the effectiveness of natural family planning extension media online, and to give knowledge of reproductive health in women. The development of Natural Family Planning media using the 4-D development model developed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel includes: Define, Design, Develop and Disseminate. Stage Develop, producing revitalized Natural Algorithm on line media based on input from experts and on-line instruments to get a knowledge of family planning and reproduction health. Furthermore, the dissemination (Disseminate). At this stage is use of Natural Family Planning extension of media online/off line that has been developed on a wider scale to conduct Natural Family Planning online/offline. Results obtained 1) Natural Family Planning media online/offline in the form of PPT Media, Video, Quiz and Forum Valid, 2) Media Extension effectively used by family planning officer of online, 3) Natural Family Planning improved female reproductive health.